PENGARUH DOSIS VAKSIN NEWCASTLEDISEASE (ND) INAKTIF TERHADAP TITER ANTIBODI PADA ITIK JANTAN - ,, Rusmiyanto; Santosa, Purnama Edy; ., Siswanto (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
The research aims to determine the effect of ND vaccine doses to the amount of antibody titers produced in the male duck, held in December 2015 until January 2016, located in the village of Sabah Balau, Subdistrict of Tanjung Bintang, District of South Lampung. The experimental design used in this study is completely randomized design (CRD) consisting of p0 control injected 0.5 ml of distilled water; p1 ND 0.1 ml dose of vaccine; p2 ND vaccine doses of 0.2 ml; p3 ND vaccine doses of 0.3 ml; p4 ND vaccine doses of 0.4 ml; and p5 ND vaccine doses of 0.5 ml. The treatment given to the male duck age of 5 days with inactive Newcastle disease (ND) vaccine. Analysis of antibody titer is done in PT. Vaksindo, Jakarta. The data were analyzed by analysis of variance on the real level of 5%. The results of this study showed that administration of inactivated ND vaccine dosesÂ give no significant effectÂ (P> 0.05) on antibody titers produced. Keywords: Antibody Titers, Doses of Inactivated ND Vaccine, Drake.